Mendorong Percepatan Lahirnya Peraturan Desa Badak Baru dan Edukasi Mengenai Sampah Bidang Lingkungan ( Garis Besar Efisiensi Pengolahan Sampah) di Desa Badak Baru, Muara Badak, Kutai Kartanegara, Kalimantan Timur - Rhemilda Nazwa; Herlinda Ragil FC; Wilda Surtina; Vitran Aldisch Anggalo; Annisa Khaidir; Adithya Zetriyadi C; Irwan Rais; Aldy Mubaraq; Azzumardi Azra; Reza Pramasta Gegana (Jurnal Pengabdian Masyarakat Waradin, 2025)
In many areas, the amount of waste continues to increase along with population growth and public consumption. One of them is in Badak Baru Village, Kutai Kartanegara. This causes serious environmental problems, such as pollution and public health. The problem that will be raised in the Community Service Program through KKN (Real Work Lectures) is increasing public awareness of the importance of good waste management. This KKN will be held from 24 June to 26 July 2024. This KKN program aims to increase public awareness of the importance of good waste management through activities carried out by KKN students. In order to create a clean and healthy environment, students carry out outreach regarding 3R (Reduce, Reuse, Recycle) and effective ways of managing it. Other activities carried out include making Madding about environmental law, and also participating in the drafting of Draft Village Regulations on Household Waste Management and Guidelines for Organizing Waste Banks in 2023, as well as other actions in the surrounding environment. Through interactive and participatory methods, this KKN program has succeeded in attracting the public's attention and increasing their understanding of the importance of reducing, reusing and recycling waste.